Underperformance of Mediastinal Lymph Node Evaluation in Resectable Non-Small Cell Lung Cancer - Apichat Tantraworasin (2018)
© 2018 The Society of Thoracic Surgeons Background: Mediastinal lymph node evaluation (MLNE) is considered to be the standard of care in curative lung cancer surgery although it is not always performed. This study identifies factors associated with patients not being evaluated (non-MLNE) in cases of resectable non-small cell lung cancer. Methods: A retrospective observational study using the Surveillance, Epidemiology, and End Results Program database was conducted. Adult patients diagnosed with non-small cell lung cancer stage I to IIIA (2004 to 2013) were included. Multilevel logistic regression analysis was performed to identify factors that were associated with non-MLNE. Results: There were 86,721 patients included in this study: 73,034 (84.2%) with MLNE and 13,687 (15.8%) without. The use of MLNE gradually increased from 82.7% in 2004 to 85.8% in 2013. In multivariable analysis, factors associated with non-MLNE included the following: age more than 75 years (adjusted odds ratio [OR adj ] 1.20, 95% confidence interval [CI] : 1.13 to 1.27); black (OR adj 1.11, 95% CI: 1.32 to 1.20); Native American/Alaskan (OR adj 1.63, 95% CI: 1.15 to 2.31); uninsured (OR adj 1.28, 95% CI: 1.05 to 1.56); residing in a low-income county (OR adj 1.12, 95% CI: 1.04 to 1.21); lesion at the middle lobe (OR adj 1.42, 95% CI: 1.29 to 1.56); lower lobe (OR adj 1.06, 95% CI: 1.01 to 1.11) or main bronchus (OR adj 2.38, 95% CI: 1.93 to 2.94); stage IA (OR adj 1.24, 95% CI: 1.17 to 1.32); sublobar resection (OR adj 11.08, 95% CI: 11.30 to 12.33); and preoperative treatment (OR adj 1.21, 95% CI: 1.08 to 1.36). Non-MLNE was less likely to occur in patients with adenocarcinoma (OR adj 0.88, 95% CI: 0.83 to 0.92) and more likely in other cell types (OR adj 1.23, 95% CI: 1.15 to 1.32), compared with squamous cell carcinoma. Conclusions: Patient demographics and socioeconomic status are associated with the decision to perform MLNE. Thoracic surgeons should access these factors and perform MLNE to accurately determine tumor stage and improve survival.